Emerging clean transportation technologies and distribution of reduced greenhouse gas emissions in Southern California - ChangKeun Park; Jiyoung Park; Simon Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
Technological innovation in transportation and the related industrial and entrepreneurial ecosystems can reduce urban environmental risks, maintaining urban environments. This study measures inter-county spillovers of the greenhouse gas (GHG) emissions impact associated with economic activity changes in the Southern California region when emerging clean transportation technologies are introduced to the region. Using a pseudo 'top-down' method, we successfully distributed the state level GHG emissions data to the county level because the GHG emissions inventory is not supported below the state level by the U.S. Environmental Protection Agency. Using the Environmental Southern California's Inter-county Social Accounting Matrix (ESCI-SAM) model and a bridge connecting two digit NAICS sectors to the GHG emissions inventory sectors, the spillover effects were measured by replacing of existing final demand for seven counties in the Southern California region. Furthermore, this study developed an extended method to discover how the effect of seven counties of the region is distributed to the rest of California excluding the seven counties, the rest of the U.S., and the rest of the world, respectively. While this study tried to measure how alternative, new clean technology freight vehicles that meet the goal of the Scoping Plan of California could spill over the region, the model developed in this study can be used for the diverse scenario simulations that involve an introduction of green economy that regulates GHG emissions of a local region.
Keywords: 650; Greenhouse gas emissions; Environmental economic model; Local spillover impacts; Spatial disaggregation